PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA SUKU DINAS TENAGA KERJA, TRANSMIGRASI DAN ENERGI KOTA ADMINISTRASI JAKARTA BARAT - Noviena Diktianti; Muhamad Guruh (Journal of Research and Publication Innovation, 2025)
This study aims to examine the influence of leadership and work motivation on employee performance at the Department of Manpower, Transmigration, and Energy of the West Jakarta Administrative City, both partially and simultaneously. The research employs a quantitative method. The population consists of all employees in the department, with a sample of 50 individuals selected using a saturated sampling technique. The data collected is quantitative and obtained from primary and secondary sources, such as observations, questionnaires, literature reviews, and documentation. The data analysis includes instrument validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation and determination tests, and hypothesis testing using t-tests and F-tests. The results show that partially, leadership has a positive and significant influence on employee performance, with a t-value of 13. 539 > 2. 008 (t-table value). Similarly, work motivation also has a positive and significant impact, with a t-value of 16. 373 > 2. 008 (t-table value). Simultaneously, leadership and work motivation have a positive and significant influence on employee performance, with an F-value of 167. 329 > 3. 20 (F-table value) and a determination value of 87. 7%. The remaining 12. 3% is influenced by other factors not included in this study